Responsible Research and Innovation: responding to the new research agenda - Pearce, Warren; Hartley, Sarah; Taylor, Alasdair (University of Nottingham, 2014)
Responsible Research and Innovation (RRI) is concerned with the nature and trajectory of research and innovation: what it can do for society and who gets to decide. RRI has been embedded in key funding institutions such as EPSRC (Engineering and Physical Sciences Research Council), and the EU’s Horizon 2020 programme and in major funding calls from other organisations. As RRI has emerged, it has been addressed in an ad hoc manner by individual projects within The University of Nottingham, such as the Synthetic Biology Research Centre and the Centre for Doctoral Training in Sustainable Chemistry.